Augmenting co2 absorption flux through a gasâliquid membrane module by inserting carbon-fiber spacers - Chen, L. (MDPI AG, 2020)
We investigated the insertion of eddy promoters into a parallel-plate gasâliquid polytetrafluoroethylene (PTFE) membrane contactor to effectively enhance carbon dioxide absorption through aqueous amine solutions (monoethanolamideâMEA). In this study, a theoretical model was established and experimental work was performed to predict and to compare carbon dioxide absorption efficiency under concurrent-and countercurrent-flow operations for various MEA feed flow rates, inlet CO2 concentrations, and channel design conditions. A Sherwood numberâs correlated expression was formulated, incorporating experimental data to estimate the mass transfer coefficient of the CO2 absorption in MEA flowing through a PTFE membrane. Theoretical predictions were calculated and validated through experimental data for the augmented CO2 absorption efficiency by inserting carbon-fiber spacers as an eddy promoter to reduce the concentration polarization effect. The study determined that a higher MEA feed rate, a lower feed CO2 concentration, and wider carbon-fiber spacers resulted in a higher CO2 absorption rate for concurrent-and countercurrent-flow operations. A maximum of 80 CO2 absorption efficiency enhancement was found in the device by inserting carbon-fiber spacers, as compared to that in the empty channel device. The overall CO2 absorption rate was higher for countercurrent operation than that for concurrent operation. We evaluated the effectiveness of power utilization in augmenting the CO2 absorption rate by inserting carbon-fiber spacers in the MEA feed channel and concluded that the higher the flow rate, the lower the power utilizationâs effectiveness. Therefore, to increase the CO2 absorption flux, widening carbon-fiber spacers was determined to be more effective than increasing the MEA feed flow rate. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.